Effects of Pre-Hospital Dexamethasone Administration on Outcomes of Patients with COPD and Asthma Exacerbation; a Cross-Sectional Study - Huabbangyang, Thongpitak; Silakoon, Agasak; Sangketchon, Chunlanee; Sukhuntee, Jareeda; Kumkong, Jukkit; Srithanayuchet, Tanut; Chamnanpol, Parinya; Meechai, Theeraphat (Archives of Academic Emergency Medicine, 2023)
Introduction: Chronic obstructive pulmonary disease (COPD) and asthma exacerbation are two common emergency situations. This study aimed to investigate the impact of pre-hospital dexamethasone initiation on treatment outcomes of these patients. Methods: In this retrospective cross-sectional and comparative study, data from the emergency medical service (EMS) care report of patients with a final diagnosis of asthma or COPD, coded with Thailand’s emergency medical triage protocol, collected between January 1, 2021, and October 31, 2022, were used. Data on baseline characteristics, emergency department length of stay (ED-LOS), and hospital admission rates were collected from electronic medical records and compared between cases with and without pre-hospital dexamethasone administration by EMS. Results: 200 patients with COPD (n = 93) and asthma (n = 107) exacerbation were enrolled. The dexamethasone-treated group had a lower but statistically non-significant hospital admission rate (71.0% versus 81.0%, absolute difference: −10%, 95% confidence interval (CI): −21.76, 1.76; p = 0.100). In patients with asthma, the dexamethasone-treated had lower median ED-LOS time (235 (IQR: 165.5–349.5) versus 322 (IQR: 238–404) minutes; p = 0.003). Dexamethasone-treated asthma patients had lower but statistically non-significant hospital admission rates (60.4% versus 78.0%, absolute difference: −17.55%, 95% CI: −34.96, −0.14; p = 0.510). In COPD patients the dexamethasone-treated and untreated groups had non-significantly lower hospital admission rates (80.8% versus 85.40%, absolute difference: −4.60%, 95% CI: −19.82, 10.63; p = 0.561) and non-significantly lower ED-LOS (232 (IQR: 150 – 346) versus 296 (IQR: 212 – 330) minutes, absolute difference: −59 (−130.81, 12.81); p = 0.106). Conclusion: The dexamethasone administration by EMS in pre-hospital setting for management of asthma and COPD patients is beneficial in reducing the ED-LOS and need for hospital admission but its effects are not statistically significant, except regarding the ED-LOS of asthma exacerbation cases.